Characterization of bone repair in rat femur after treatment with calcium phosphate cement and autogenous bone graft - Leite Mauro G; Martins Gustavo L; Ponzoni Deise; Corsetti Adriana; Puricelli Edela; Santos Luis A (Head & Face Medicine, 2010)
Abstract Background In this study, the biocompatibility, stability and osteotransductivity of a new cement based on alpha-tricalcium phosphate (alpha-TCP) were investigated in a bone repair model using a rat model. Methods The potential of alpha-TCP on bone repair was compared to autogenous bone grafting, and unfilled cavities were used as negative control. Surgical cavities were prepared and designated as test (T), implanted with alpha-TCP blocks; negative control (C - ), unfilled; and positive control (C + ), implanted with autogenous bone graft. Results were analyzed on postoperative days three, seven, 14, 21 and 60. Results The histological analyses showed the following results. Postoperative day three: presence of inflammatory infiltrate, erythrocytes and proliferating fibroblasts in T, C - and C + samples. Day seven: extensive bone neoformation in groups T and C + , and beginning of alpha-TCP resorption by phagocytic cells. Days 14 and 21: osteoblastic activity in the three types of cavities. Day 60: In all samples, neoformed bone similar to surrounding bone. Moderate interruption on the ostectomized cortical bone. Conclusions Bone neoformation is seen seven days after implantation of alpha-TCP and autogenous bone. Comparison of C - with T and C + samples showed that repair is faster in implanted cavities; on day 60, control groups presented almost complete bone repair. Alpha-TCP cement presents biocompatibility and osteotransductivity, besides stability, but 60 days after surgery the cavities were not closed.